Meiotic recombination between two polymorphic restriction sites within the beta globin gene cluster. Issue 1 (February 1986) - Old, J M; Heath, C; Fitches, A; Thein, S L; Jeffreys, A J; Petrou, M; Modell, B; Weatherall, D J
Abstract : Analysis of beta globin gene haplotypes for prenatal diagnosis of beta thalassaemia has revealed a recombination event within the beta globin gene cluster. Both a change in the AvaII polymorphic site within the beta globin gene and a change in the phenotype of the beta globin gene were observed. Paternity was established by the pedigree analysis of hypervariable 'minisatellite' DNA polymorphisms and the most probable explanation of the recombination event is a crossover between the psi beta globin gene and the beta globin gene. The data provide direct evidence in support of a DNA region 3' to the beta globin gene with a recombination frequency much higher than expected, and have important implications for the prenatal diagnosis of beta thalassaemia by linked restriction fragment length polymorphisms.